Optimalisasi Komunikasi Layanan Kebersihan melalui Chatbot: Studi Empiris di Desa Sindangjawa Kabupaten Cirebon - Leni Leni Rohida S.Sos. Rohida; Eteh Resa (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2026)
The primary issue of this research is the communication challenges in managing illegal waste in rural areas, which require a rapid response. Conventional sanitation service communications have proven slow and unresponsive, hampering the optimization of rapid and effective public services. The objective of this empirical study is to analyze the optimization of sanitation service communications through the implementation of a chatbot in Sindangjawa Village from a user acceptance perspective. The method used was a quantitative explanatory survey design, adopting the Technology Acceptance Model (TAM) framework. Data were collected from Sindangjawa resident respondents using a Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM). The results indicate that Perceived Usefulness and Perceived Ease of Use (PEU) have a positive and significant influence on Chatbot Use Intention. Communication optimization occurs through drastic operational efficiencies, as evidenced by a reduction in initial response times and the ability to automate repetitive tasks. In conclusion, chatbots are a strategic tool for improving public service performance at the village level, but long-term adoption must be supported by quality problem-solving skills and mitigation of ICT barriers.